“No Viral no Justice” dalam Perspektif Etika Komunikasi Islam - Hijrayanti Sari Muin; Muhammad Anshar (CV Kalimasada Group, 2026)
The “no viral, no justice” phenomenon reflects the distrust that some Indonesians have toward the formal law enforcement system, leading them to use virality on social media as an alternative means of obtaining justice. This study aims to analyze this phenomenon from the perspective of Islamic communication ethics by examining relevant Islamic principles such as tabayyun, the prohibition against backbiting (ghibah) and spying (tajassus), the obligation of hisbah, and the principle of maslahat-mafsadat. The method used is descriptive qualitative research employing a library research approach, through interpretive analysis of scholarly literature, exegetical texts, hadith sources, and contemporary studies on Islamic communication ethics. The research findings indicate that the viral dissemination of information to demand justice is justifiable in Islam provided it meets four conditions: the information has been verified (tabayyun), the purpose is purely to prevent wrongdoing (hisbah), official channels have been exhausted without result, and the dissemination is carried out proportionally. Conversely, the viral spread of information that contains unverified defamatory content, excessively exposes the victim’s privacy, or is motivated by purposes other than justice is categorized as a violation of Islamic communication ethics. This article emphasizes that the struggle for justice through social media must always be grounded in Islamic communication ethics so as not to give rise to new injustices.